Course of Health Care Costs before and after Psychiatric Inpatient Treatment: Patient-Reported vs. Administrative Records - Nadja Zentner; Ildiko Baumgartner; Thomas Becker; Bernd Puschner (Kerman University of Medical Sciences, 2015)
Background There is limited evidence on the course of health service costs before and after psychiatric inpatient treatment, which might also be affected by source of cost data. Thus, this study examines: i) differences in health care costs before and after psychiatric inpatient treatment, ii) whether these differences vary by source of cost-data (self-report vs. administrative), and iii) predictors of cost differences over time. Methods Sixty-one psychiatric inpatients gave informed consent to their statutory health insurance company to provide insurance records and completed assessments at admission and 6-month follow-up. These were compared to the self‐reported treatment costs derived from the "Client Socio-demographic and Service Use Inventory" (CSSRI‐EU) for two 6‐month observation periods before and after admission to inpatient treatment to a large psychiatric hospital in rural Bavaria. Costs were divided into subtypes including costs for inpatient and outpatient treatment as well as for medication. Results Sixty-one participants completed both assessments. Over one year, the average patient‐reported total monthly treatment costs increased from € 276.91 to € 517.88 (paired Wilcoxon Z = ‐2.27; P = 0.023). Also all subtypes of treatment costs increased according to both data sources. Predictors of changes in costs were duration of the index admission and marital status. Conclusion Self-reported costs of people with severe mental illness adequately reflect actual service use as recorded in administrative data. The increase in health service use after inpatient treatment can be seen as positive, while the pre-inpatient level of care is a potential problem, raising the question whether more or better outpatient care might have prevented hospital admission. Findings may serve as a basis for future studies aiming at furthering the understanding of what to expect regarding appropriate levels of posthospital care, and what factors may help or inhibit post-discharge treatment engagement. Future research is also needed to examine long-term effects of inpatient psychiatric treatment on outcome and costs.